2023
DOI: 10.48550/arxiv.2301.12490
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How does HCI Understand Human Autonomy and Agency?

Dan Bennett,
Oussama Metatla,
Anne Roudaut
et al.

Abstract: Human agency and autonomy have always been fundamental concepts in HCI. New developments, including ubiquitous AI and the growing integration of technologies into our lives, make these issues ever pressing, as technologies increase their ability to influence our behaviours and values. However, in HCI understandings of autonomy and agency remain ambiguous. Both concepts are used to describe a wide range of phenomena pertaining to sense-of-control, material independence, and identity. It is unclear to what degre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…But how exactly do HCI researchers understand agency? Bennett et al [7] surveyed 161 publications across 30+ years of HCI and identified 4 key aspects of agency: self-causality/identity, material/experiential, interaction time-scales, and tradeoff between independence and interdependence. In our work, we draw mostly from the aspect of self-causality/identity 4 , which refers to the level and directness of a user's decision-making and action execution in line with their own values.…”
Section: Agency and Algorithms On Social Mediamentioning
confidence: 99%
See 4 more Smart Citations
“…But how exactly do HCI researchers understand agency? Bennett et al [7] surveyed 161 publications across 30+ years of HCI and identified 4 key aspects of agency: self-causality/identity, material/experiential, interaction time-scales, and tradeoff between independence and interdependence. In our work, we draw mostly from the aspect of self-causality/identity 4 , which refers to the level and directness of a user's decision-making and action execution in line with their own values.…”
Section: Agency and Algorithms On Social Mediamentioning
confidence: 99%
“…P9[IG]'s statement demonstrated a desire for self-causality, a key aspect of agency defined by the ability to make personal choices and see these decisions reflected in an outcome in line with their values and goals [7]. Participants even prioritized self-causality above content enjoyment: P8[IG] said that while they sometimes enjoyed the algorithm's suggested posts, they "would put it towards the end [of the feed], because it's not something I've decided I want to see."…”
Section: 25mentioning
confidence: 99%
See 3 more Smart Citations